2014
DOI: 10.1016/j.febslet.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional relevance of the internal hydrophobic cavity of urate oxidase

Abstract: a b s t r a c tUrate oxidase from Aspergillus flavus is a 135 kDa homo-tetramer which has a hydrophobic cavity buried within each monomer and located close to its active site. Crystallographic studies under moderate gas pressure and high hydrostatic pressure have shown that both gas presence and high pressure would rigidify the cavity leading to an inhibition of the catalytic activity. Analysis of the cavity volume variations and functional modifications suggest that the flexibility of the cavity would be an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
1
25
2
Order By: Relevance
“…It was observed that a moderate pressure of Xe gas induces a small contraction of the active site and a small expansion of the adjacent hydrophobic cavity, with Xe atoms populating the latter. With pressure exerted by O 2 gas, a similar phenomenon was observed, but no O 2 could be detected inside the above hydrophobic cavity, while a single O 2 molecule was found at the active center, over the substrate, on the internal protein side . It was also observed that high hydrostatic pressure has the reverse effect, contracting the active site, while expanding the nearby hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…It was observed that a moderate pressure of Xe gas induces a small contraction of the active site and a small expansion of the adjacent hydrophobic cavity, with Xe atoms populating the latter. With pressure exerted by O 2 gas, a similar phenomenon was observed, but no O 2 could be detected inside the above hydrophobic cavity, while a single O 2 molecule was found at the active center, over the substrate, on the internal protein side . It was also observed that high hydrostatic pressure has the reverse effect, contracting the active site, while expanding the nearby hydrophobic cavity.…”
Section: Introductionmentioning
confidence: 54%
“…On these bases, a first model for MD was built with a molecule of O 2 (represented at VdW size in red color in Fig. ) above 5 , toward the inside of the homotetramer, as indicated by the X‐ray diffraction studies . This model was used to investigate how O 2 can leave the protein under an accelerated form of MD, where expulsion of O 2 is aided by an external randomly oriented force (random acceleration MD, in short RAMD , as detailed below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPMX allows to determine the most flexible parts of a protein in relation with its internal cavity modifications. The analyses of protein structures determined under high hydrostatic pressure have revealed that the main pressure-induced structural effects occur on the volumes of cavities which are reduced 3235 . Coarse-grained simulations allow to investigate the mechanical properties of the proteins, in particular those of the frontier residues lining internal cavities, and highlight their mechanical nucleus 3640 .…”
Section: Introductionmentioning
confidence: 99%
“…The position of O 2 observed here is consistent with that of room-temperature O 2 -pressurization experiments. [11] Peroxide breakdown also brings about a reorganization of the solvent around the organic moiety with the appearance of a solvent molecule (W2) bound to the O8 atom of the substrate. Raman analysis shows that peroxide rupture causes the 605 cm −1 ‘signature band’ to selectively decrease in a dose-dependent manner (Figure 4 b,c) consistent with our QM/MM calculations that assign this band to the stretching of the C5=Op1 bond.…”
mentioning
confidence: 99%